Monthly At-Home Computerized Cognitive Testing to Detect Diminished Practice Effects in Preclinical Alzheimer's Disease - Jutten, Roos J.; Rentz, Dorene M.; Fu, Jessie F.; Mayblyum, Danielle V.; Amariglio, Rebecca E.; Buckley, Rachel F.; Properzi, Michael J.; Maruff, Paul; Stark, Craig E.; Yassa, Michael A.; Johnson, Keith A.; Sperling, Reisa A.; et al. (Frontiers in Aging Neuroscience, 2022)
Introduction: We investigated whether monthly assessments of a computerized cognitive composite (C3) could aid in the detection of differences in practice effects (PE) in clinically unimpaired (CU) older adults, and whether diminished PE were associated with Alzheimer’s disease (AD) biomarkers and annual cognitive decline. Materials and Methods: N=114 CU participants (age 77.6±5.0, 61% female, MMSE 29±1.2) from the Harvard Aging Brain Study completed the self-administered C3 monthly, at-home, on an iPad for over one year. At baseline, participants underwent in-clinic Preclinical Alzheimer’s Cognitive Composite-5 (PACC5) testing, and a subsample (n=72, age=77.8±4.9, 59% female, MMSE 29±1.3) had one-year follow-up in-clinic PACC5 testing available. Participants had undergone PIB-PET imaging (0.99±1.6 years before at-home baseline) and Flortaucipir PET imaging (n=105, 0.62±1.1 years before at-home baseline). Linear mixed models were used to investigate change over months on the C3 adjusting for age, sex, and years of education, and to extract individual covariate-adjusted slopes over the first three months. We investigated the association of 3-month C3 slopes with global amyloid burden and tau deposition in eight predefined regions of interest, and conducted Receiver Operating Curve analyses to examine how accurately 3-month C3 slopes could identify individuals that showed >0.10 SD annual decline on the PACC-5. Results: Overall, individuals improved on all C3 measures over 12 months (β=0.23, 95%CI=[0.21-0.25], p<.001), but improvement over the first 3 months was greatest (β=0.68, 95%CI=[0.59-0.77], p<.001), suggesting stronger PE over initial repeated exposures. However, lower PE over 3 months were associated with more global amyloid burden (r=-.20, 95%CI=[-0.38 – -0.01], p=.049) and tau deposition in the entorhinal cortex (r=-.38, 95%CI=[-0.54 – -0.19], p<.001) and inferior-temporal lobe (r=-.23, 95%CI=[-0.41 – -0.02], p=.03). 3-month C3 slopes exhibited good discriminative ability to identify PACC-5 decliners (AUC 0.91, 95%CI=[0.84 – 0.98]), which was better than baseline C3 (p<.001) and baseline PACC-5 scores (p=.02). Conclusion: While PE are commonly observed among CU adults, diminished PE over monthly cognitive testing are associated with greater AD biomarker burden and cognitive decline. Our findings imply that unsupervised computerized testing using monthly retest paradigms can provide rapid detection of diminished PE indicative of future cognitive decline in preclinical AD.